Is Animal-Assisted Therapy for Minimally Conscious State Beneficial? A Case Study - Boitier, Jacqueline P.; Huber, Marion; Saleh, Christian; Kerry, Matthew J.; Hund-Georgiadis, Margret; Hediger, Karin (Frontiers in Psychiatry, 2020)
Objective The goal of this single case study was to qualitatively investigate the effects of animal-assisted therapy in a patient in a minimally conscious state. Method We present a 28-year-old female patient in a minimally conscious state following polytrauma after a sports accident leading to cerebral fat embolism causing multiple CNS ischemic lesions. She received eight animal-assisted therapy sessions and eight paralleled control therapy sessions over 4 weeks. We investigated the reactions of the patient during these sessions via qualitative behavior analysis. Results The patient showed a broader variability and higher quality of behavior during animal-assisted therapy compared to control therapy sessions. Conclusion The observed behavioral changes showed higher arousal and increased awareness in the presence of an animal. The presented case supports the assumption that animal-assisted therapy can be a beneficial treatment approach for patients in a minimally conscious state.